Use of a Simple Fabrication Process to Produce A Biosensor: The 3-hydroxybutyrate Dehydrogenase Case - Coutinho, Isabel Cristina Ribau Fernandes (2019)
This study was aimed to construct a biodegradable but reliable 3-β-hydroxybutyrate biosensor. In this context a versatile paper based biosensor, quickly, easily and cheaply fabricated is reported. The procedure of fabrication is based on the assumption that the introduction of the enzyme in the carbon ink will allow enzyme stabilization and facilitate the study of the catalysis of enzymes and the detection of substrates. To prove this concept we use the enzyme 3-hydroxybutyrate dehydrogenase, in aqueous solution. This enzyme was chosen because it catalyzes the 3-β-hydroxybutyrate, which results from ketoacidosis. The quantification this substance in the diabetics’ blood is very important as it can increase the reliability of the diagnosis of glycaemia. To prove the multi-use of this biosensor we not only study the redox process in steady state and during the catalytic process, but also detected and quantify the 3-β-hydroxybutyrate. Our results showed that it was possible to study the redox process that occurred during the catalysis and to confirm the amino acid residues that participate in it. It was also observed that glucose and ascorbic acid can interfere in the detection and quantification of the 3-β-hydroxybutyrate, what should be in mind when the quantification of the 3-β-hydroxybutyrate is made in blood samples.